Pots, Pans, and People: Ceramic Ecology in West Mexico - Eduardo Williams (Papers from the Institute of Archaeology, 1992)
Little is known about the interrelationship of environment and ceramic specialization, and many questions still remain to be answered, for example: What factors favor or limit the development of ceramic specialization? Why did pottery apparently arise in some places and not in others? One way to answer these questions is to explore the environmental interrelationships of a modern pottery-making community and apply the results to the prehistory of that region
Keywords: ceramics; pottery